The Impact of High Temperatures on Performance in Work-Related Activities - Matteo Picchio; Jan C. van Ours (Institute of Labor Economics (IZA), 2023)
High temperatures can have a negative effect on work-related activities. Labor productivity may go down because mental health or physical health is worse when it is too warm. Workers may experience difficulties concentrating or they have to reduce effort in order to cope with heat. We investigate how temperature affects performance of male professional tennis players. We use data about outdoor singles matches from 2003 until 2021. Our identification strategy relies on the plausible exogeneity of short-term daily temperature variations in a given tournament from the average temperature over the same tournament. We find that performance significantly decreases with ambient temperature. The magnitude of the temperature effect is age-specific and skill-specific. Older and less-skilled players suffer more from high temperatures than younger and more skilled players do. The effect of temperature on performance is smaller when there is more at stake. Our findings also suggest that there is adaptation to high temperatures: the effects are smaller if the heat lasts for several days.
Keywords: J24; J81; Q51; Q54; 330; climate change; temperatures; tennis; performance; productivity